The Importance of Thiopurine S-Methyltransferase Gene Analysis Before Azathioprine Therapy. Issue 4 (July 2020) - Gürbüz, Gürkan; Edizer, Selvinaz; Yılmaz, Ünsal; Ünalp, Aycan
Abstract : Abstract: Neuromyelitis optica is an inflammatory central nervous system syndrome associated with serum aquaporin-4 IgG antibody. Optic nerve and spinal cord involvement is typical. We report a 9-year-old girl with a diagnosis of neuromyelitis optica, who developed azathioprine-induced pancytopenia that was subsequently found to be caused by thiopurine-methyltransferase mutation.